Classification and Simulation Method for Piezoelectric PVDF Sensors. (2016) - Baumgärtel, Klaas Hauke; Zöllner, Daniel; Krieger, Karl-Ludwig
Abstract: The piezoelectric polymer Polyvinylidene fluoride (PVDF) holds the potential to be the core material of novel structure-borne sound sensors not only in research but also in industrial applications. This paper will give an overview of possibilities when PVDF is useful and when PVDF reaches its limits of applicability. To do so, a state of the art about current applications of PVDF will be given. Furthermore, the consecutive equations and an experimental setup for the classification of the piezoelectric constants and Young's moduli over frequency and temperature will be presented. A simplified FE simulation method will also be shown to model PVDF film sensors by computer aided design.